Pelaksanaan Program Keluarga Harapan (PKH) terhadap Kehidupan Keluarga Penerima Manfaat (KPM) di Desa Gantar Kabupaten Indramayu - Iva Nurfadillah; Hamdan Hamdani (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This research is motivated by the persistently high poverty rate in Indonesia, which is not only related to low community income, but also limited access to education, health, and fulfillment of basic needs. Therefore, the government introduced the Family Hope Program (PKH) as a conditional cash assistance-based social protection effort to improve the welfare of the poor. This study aims to analyze the implementation of PKH on the lives of Beneficiary Families (KPM) in Gantar Village, Indramayu Regency using descriptive qualitative research methods based on social welfare theory. The method used in this study is qualitative with data collection techniques through interviews, observations, and documentation of PKH facilitators and KPM as primary and secondary data sources. The results of the study indicate that the implementation of PKH not only functions as economic assistance, but also as an instrument of social empowerment through stages of data collection, socialization, mentoring, and Family Capacity Building Meeting (P2K2) activities that have a positive impact on community life. The research findings reveal that PKH helps fulfill daily needs, increases access to children's education, family health awareness, and strengthens household economic conditions, although there are still obstacles such as inaccurate data, low community understanding, and limited participation in mentoring activities. The implications of this research show that the success of PKH is largely determined by the quality of social assistance, data validity, and increasing community understanding so that the program can run more effectively and sustainably in improving family welfare.